1937
DOI: 10.1139/f37-029
|View full text |Cite
|
Sign up to set email alerts
|

Some Characteristics of the Enzymes of the Pyloric Caeca of Cod and Haddock

Abstract: Investigation of fish enzymes for leather bates reveals that those of the pyloric caeca show their greatest influence on casein and collagen at hydrogen ion concentrations of approximately pH 8. The protease showed its maximum activity towards casein at a temperature of 45"C. Ammonium salts at certain concentrations increased the rate of hydrolysis of collagen by about 40 per cent, but had no like stimulating effect on the hydrolysis of casein. A comparison showed that pyloric caeca enzymes were just .as satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1969
1969
1989
1989

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…8OC. Earlier studies have shown the presence of trypsin, or a trypsin-like enzyme, in this fish species, but the enzyme was neither fully purified nor characterized kinetically with respect to temperature dependence [9,101. Trypsin or trypsin-like enzymes have been characterized from other fishes [ll -131, including two arctic species, the capelin [14] and Greenland cod [15, 161. The present report describes the results obtained from studies on trypsin isolated from the pyloric caeca of Atlantic cod, the site of exocrine pancreatic tissue in the cod [17].…”
mentioning
confidence: 95%
“…8OC. Earlier studies have shown the presence of trypsin, or a trypsin-like enzyme, in this fish species, but the enzyme was neither fully purified nor characterized kinetically with respect to temperature dependence [9,101. Trypsin or trypsin-like enzymes have been characterized from other fishes [ll -131, including two arctic species, the capelin [14] and Greenland cod [15, 161. The present report describes the results obtained from studies on trypsin isolated from the pyloric caeca of Atlantic cod, the site of exocrine pancreatic tissue in the cod [17].…”
mentioning
confidence: 95%